Minat Global dalam Bidang Konservasi Gigi Sebelum dan Masa Pandemi COVID-19: Analisis Data Google Trends - Salmia Atika Desri; Hanim Khalida Zia; Widyawati Widyawati; Valendriyani Ningrum (FORIKES, 2022)
The COVID-19 pandemic situation has caused changes in needs and new challenges in dentistry services. Toothache often requires immediate treatment. The source of pain is generally caused by cavities that require conservative measures. The aim of this research is to analyze the changing global interest in dental conservation before and during the COVID-19 pandemic. This research used analytic observational method. The secondary data used came from Relative Search Volume (RSV) Google Trends, from all countries in the world that access search data through the Google database. This study used five keywords related to the field of tooth conservation, namely